Orphanhood and Parenthood in Joseph and Aseneth - Hays, Nathan ca. 21. Jh. (Journal for the study of the pseudepigrapha, 2017)
In the romance Joseph and Aseneth, Aseneth identifies herself as an orphan abandoned by her parents (e.g., 11.3-5; 12.5; 13.1-2). The problem, however, is that she consistently maintains cordial relations with her family. This article addresses this discrepancy by analyzing the rhetorical function of the orphanhood language in light of the parenthood imagery running throughout the work. The romance presents people as belonging to the families of either God or the devil (12.9-11). Aseneth's self-identification as an orphan both signals her total separation from the family of the devil and prepares Aseneth for full incorporation into the family of God by placing her into the category of marginalized people over whom God exercises paternal care (e.g., 11.13; 12.13). The orphanhood and parenthood language thus justifies the acceptance of non-Jews into the chosen community in a way that could have appealed to some communities of Jews or Christians.